2019
DOI: 10.1016/j.amsu.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Trends of mastectomy and breast-conserving surgery and related factors in female breast cancer patients treated at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, 2009–2017: A retrospective cohort study

Abstract: Background Breast cancer is the most common cancer in women and accounts for 14.7% of cancer-related deaths among females worldwide. Its core management includes surgical removal of the tumor either by breast-conserving surgery (BCS) or mastectomy. Choosing between these two procedures may be influenced by factors that are not studied in our region. We aimed to determine the prevalence of BCS and mastectomy and the factors that may influence the choice of procedure. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
(52 reference statements)
4
14
0
Order By: Relevance
“…Age has shown varied effects on breast cancer surgical management across the previous literature, and most of them have indicated that older age is associated with an increased uptake of mastectomy, which is consistent with our results (Huang et al, 2016;Al-Gaithy et al, 2019;Chen et al, 2019). We found that women who were married and had at least one child were significantly more likely to undergo a mastectomy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age has shown varied effects on breast cancer surgical management across the previous literature, and most of them have indicated that older age is associated with an increased uptake of mastectomy, which is consistent with our results (Huang et al, 2016;Al-Gaithy et al, 2019;Chen et al, 2019). We found that women who were married and had at least one child were significantly more likely to undergo a mastectomy.…”
Section: Discussionsupporting
confidence: 91%
“…3) Types of surgical procedures. In this study, we considered mastectomy to include simple mastectomy, modified radical mastectomy, total mastectomy or skin/areola/nipple-sparing mastectomy, not otherwise specified (Al-Gaithy et al, 2019). The rate of mastectomy was defined as the percentage of mastectomy among all breast cancer cases.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Mastectomy was the main type of surgery for both the first and second cancers because of late recognition and advanced stages at diagnosis ( Table 2 ). Although general consensus on the optimal surgery approach for patients with bilateral breast cancer is not well established, recent studies have shown that bilateral mastectomy has been performed more frequently in synchronous bilateral cancer [ 5 , 32 , 33 ]. Clinical treatment of bilateral cancer including breast surgery has been suggested to be in line with unilateral breast cancer because the indication, contraindication, and prognosis are similar in patients with bilateral breast cancer treated with breast conservation surgery [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adjuvant radiotherapy given to mastectomy site and axilla increases risk of impairment of shoulder function. 9 Upper extremity disability (UED) is one among the foremost troublesome longterm complications of carcinoma treatment 10,11,12 . It is now well established that carcinoma survivors have a high prevalence of arm/shoulder impairments which will persist for several years, and are related to long-term activity limitations, participation restriction, and general quality of life impact.…”
Section: Introductionmentioning
confidence: 99%